NutriMinder Aplikasi Pemantauan Gizi dan Panduan Makanan dengan Informasi yang Mudah Dipahami - Muhamad Hidayat,; Anak Agung Istri Ngurah Eka Karyawati, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Effective nutritional monitoring to improve public health has become increasingly important in the modern era. NutriMinder is an application intended to provide easy-to-understand food guidance and help users monitor their daily nutritional intake. In this article, the NutriMinder algorithm and application design are discussed. It includes initialization, user registration, food logging, nutrition monitoring, food recommendations, analysis and reports, and user interface.
Keywords: nutrition monitoring, food guides, health apps, NutriMinder, fuzzy logic